Penuntutan Requistoir Bagi Pelaku Tindak Pidana Narkotika - Fauzi Iswahyudi (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Prosecution of an event or criminal act, including narcotics crime is a function carried out by the Prosecutor's Office, in this case by the public prosecutor. Prosecution is the act of the public prosecutor delegating a criminal case to a competent district court in terms of and according to the method stipulated in the Criminal Procedure Code. The prosecution of the defendant in a narcotics crime case, it is not uncommon for the prosecutor to prosecute with varying demands even though the provisions of the Article charged against the defendant are the same. The difference in demands for punishment in prosecution carried out by public prosecutors is certainly based on various considerations and can be accounted for. This writing uses normative juridical legal research methods (normative research) with descriptive analytical research specifications that use secondary data. The procedure of data collection is in the form of documentation of notes or quotations, search of legal literature, books and others related to the identification of problems both offline and online, which are then analyzed through the content analysis method (centent analysis method).